2016
DOI: 10.3389/fneur.2016.00183
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation of Bone Marrow Mesenchymal Stem Cells into Neuron-Like Cells by Cerebrospinal Fluid Improves Motor Function of Middle Cerebral Artery Occlusion Rats

Abstract: Bone marrow mesenchymal stem cells (BMSCs) represent a promising tool for stem cell-based therapies. However, the majority of BMSC transplants only allow for limited recovery of the lost functions. We previously found that human cerebrospinal fluid (hCSF) is more potent than growth factors in differentiating human BMSCs into neuron-like cells in vitro. In this study, we studied the effect of transplantation of rat BMSC-derived neuron-like cells (BMSC-Ns) induced by hCSF into rat brain with middle cerebral arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…BMSCs and ADSCs are known to differentiate into neurons ( 22 , 23 ). In our study, nestin, a neural precursor stem cells marker, and β-tubulin III, an immature neuronal marker, were expressed in native BMSCs and ADSCs, which suggested that both MSCs retained a native potential for neuronal differentiation and were in conformity with other studies ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs and ADSCs are known to differentiate into neurons ( 22 , 23 ). In our study, nestin, a neural precursor stem cells marker, and β-tubulin III, an immature neuronal marker, were expressed in native BMSCs and ADSCs, which suggested that both MSCs retained a native potential for neuronal differentiation and were in conformity with other studies ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are a group of heterogeneous multipotent adult stem cells 22,23 can be differentiated into chondrocytes 24,25 , adipocytes 26 , myocytes 27,28 , endothelial cells 29,30 , and neurons 3134 . The main advantages of adipose-derived stem cells (ADSCs), include the feasibility of autologous transplantation, the ability to secrete neurotrophic factors and cytokines to promote the survival of endogenous cells, and suppress the inflammatory response to facilitate tissue repair 17,35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…MSCs represent a powerful tool in the field of regenerative medicine. The results of in vitro studies showed that MSCs are capable of differentiating into neuron‐like cells . The therapeutic benefits of MSC transplantation have been reported in TBI animal models and clinical trial.…”
Section: Mesenchymal Stromal Cells In Traumatic Brain Injurymentioning
confidence: 96%
“…The results of in vitro studies showed that MSCs are capable of differentiating into neuron-like cells. 41,42 The therapeutic benefits of MSC transplantation have been reported in TBI animal models and clinical trial. MSCs isolated from bone marrow decreased blood-brain barrier permeability, inhibit activated microglia/macrophage accumulation in the thalamic region and promote neurogenesis in a rat model of TBI.…”
Section: Mesenchymal Stromal Cells In Traumatic Brain Injurymentioning
confidence: 99%